Rare Giant Granular Cell Ameloblastoma: A Case Report and an Immunohistochemical Study - Santosh Hunasgi; Anila Koneru; Dinesh Singh Chauhan; Yadavalli Guruprasad (Hindawi Limited, 2013)
Aims. The aim is to present a case of rare giant granular cell ameloblastoma and to review the pertinent literature highlighting the molecular aspects of its pathogenesis by analyzing the expression of CD-68, Bcl-2, and β-catenin. Methods. H and E stained sections showed large odontogenic islands showing peripheral ameloblast-like cells and central stellate reticulum-like cells with extensive granular cell transformation surrounded by fibrous stroma. Polyclonal rabbit anti-CD 68, anti-Bcl2, and anti-β-catenin were stained immunohistochemically. Results. CD-68 showed a moderate to strong staining intensity in granular cells. Moderate staining of Bcl-2 was expressed by the peripheral columnar cells of tumor islands and negative in the granular cells. Expression of β-catenin was generally weak, except for only the focal areas that showed a moderate staining intensity and weak in peripheral cells. Conclusion. The present case of giant granular cell ameloblastoma is a rare entity. Development of monstrous size is indicative of ameloblastomas persistent growth. Granular cell transformation in ameloblastomas probably occurs as a consequence of extensive molecular changes. Immunohistochemical studies help us to know the pathogenesis of this granular cell ameloblastoma. Therefore, an effort has been made here to study the expression of Bcl-2, CD-68, and β-catenin.